2005
DOI: 10.1007/s11274-004-3045-z
|View full text |Cite
|
Sign up to set email alerts
|

Rapid screening of Aspergillus terreus mutants for overproduction of lovastatin

Abstract: SummaryA novel rapid screening method is demonstrated for isolating lovastatin-overproducing strains of Aspergillus terreus. The screening methodology, based on the activity of lovastatin against the yeast Candida albicans, is nearly three times as fast as the selection methods used earlier. The new 6-h assay shows a linear correlation between the quantity of lovastatin generated by A. terreus isolates and the inhibition zones obtained on plates of C. albicans. The new technique is less expensive and requires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…It is likely that an inhibition zone was produced because A. terreus secrets metabolites that interfere with the growth of P. aphanidermatum . Ferrón et al (2005) and Wang et al (2011) reported the production of terremides A and B and lovastatin by A. terreus that were found responsible for the production of inhibition zones. In our study, the use of CF from A. terreus isolates resulted in electrolyte leakage in P. aphanidermatum mycelium and also interfered with oospore production in P. aphanidermatum .…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that an inhibition zone was produced because A. terreus secrets metabolites that interfere with the growth of P. aphanidermatum . Ferrón et al (2005) and Wang et al (2011) reported the production of terremides A and B and lovastatin by A. terreus that were found responsible for the production of inhibition zones. In our study, the use of CF from A. terreus isolates resulted in electrolyte leakage in P. aphanidermatum mycelium and also interfered with oospore production in P. aphanidermatum .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the methods used for the hyper-production of statins in A. terreus species include: Chemical mutagenesis, involving use of mutagenic chemicals such as ethyl methanesulfonate (EMS) and N -methyl- N ’-nitro- N -nitrosoguanidine (NTG) [ 45 , 82 , 83 ] and Physical mutagenesis, involving the use of radiation such as high radiation heavy ion beams and ultraviolet radiation [ 57 , 71 ]. …”
Section: Exploitation Of a Terreus For Statin mentioning
confidence: 99%
“…Chemical mutagenesis, involving use of mutagenic chemicals such as ethyl methanesulfonate (EMS) and N -methyl- N ’-nitro- N -nitrosoguanidine (NTG) [ 45 , 82 , 83 ] and…”
Section: Exploitation Of a Terreus For Statin mentioning
confidence: 99%
“…The bioassay method for screening the lovastatin producing fungi was adopted from Kumar et al (2000) [25] and Vilches et al (2005) [26] using Saccharomyces cerevisiae as indicator organisms, and the ability of lovastatin to inhibit fungal growth was tested. Yeast growth inhibition was performed by seeding 15 ml of glucose yeast peptone agar medium with 0.25 ml of yeast culture (S. cerevisiae).…”
Section: Lovastatin Detectionmentioning
confidence: 99%